Gross pathology and its relationship with histopathology of amoebic gill disease (AGD) in farmed Atlantic salmon, Salmo salar L - Mark Adams; Ellard, K; Barbara Nowak (2004)
Gross pathological assessment of amoebic gill disease (AGD) is the only non-destructive, financially viable method for rapid and broad-scale disease management of farmed Atlantic salmon, Salmo salar L., in Tasmania. However, given the presumptive nature of this diagnosis, the technique has been considered questionable. This study investigated the degree of conformity between clinical signs and histological lesions observed in a commercial setting. Three groups of Atlantic salmon (n = 42, 100 and 100, respectively) were collected from various farm sites in southern Tasmania between December 2001 and April 2003. Micro-stereoscopic analysis showed that grossly affected tissue regions correspond to areas of hyperplastic lamellar fusion, generally in association with attached Neoparamoeba sp. Agreement between gross signs of AGD and histopathological diagnosis was compared. Kappa analysis indicated moderate to good agreement between methods (Îº = 0.52-0.74). Individual cases of disagreement were further scrutinized and several factors were found to influence the level of agreement between the two methods. Stage of disease development, lesions derived from other pathogens, assessor interpretation/ experience, sampling methods, histological technique and/or experience were potential confounding factors. It was concluded that clinical diagnosis is acceptable as a farm-monitoring; tool only. Removal of grossly affected tissue and subsequent histological examination is recommended to improve diagnostic accuracy.